Acute Dysuria in Women: Letter (The New England journal of medicine, 1984)
To the Editor: In the February 9 issue of the Journal , Komaroff makes the point that the laboratory assessment of pyuria based on a centrifuged urine sediment is subject to several sources of error.1 He cites Stamm et al.2 as suggesting that the number of leukocytes to be considered as evidence of clinically important pyuria is 8 or more per milliliter of uncentrifuged urine, using the leukocyte counting chamber. In men, a diagnosis of nongonococcal urethritis is based on a finding of more than 4 leukocytes per field in five oil-immersion fields.1 My colleagues and I have found a similar minimal concentration in conjunctival smears from neonates with purulent conjunctivitis (unpublished data), as have Brunham et al. in studies of mucopurulent cervicitis.2 I am unaware of such data concerning the normal concentration of leukocytes in urethral smears from women with urethritis of various causes, but 1 would be surprised if it were not the same as for these other conditions. [...]the clinician evaluating a patient with acute dysuria has two options for diagnosing a probable sexually acquired infection: the urethral and the endocervical smear with Grain's stain. Direct staining of elementary bodies of C. trachomatis with a fluorescein-labeled monoclonal antibody is now available,3 which in our hospital costs less than a urine culture and colony count ($12.50 vs. $23.00). Exclusion criteria included signs or symptoms of vaginitis, allergy to penicillin, symptoms lasting more than seven days, signs of pyelonephritis (fever, flank tenderness, and vomiting), antibiotic use within one month, a concomitant diagnosis of renal disease or diabetes mellitus, pregnancy, and age less than 12 years.